(untitled) (American Journal of Technology and Applied Sciences, 2022)
Learning to speak necessarily involves the formation of skills to build up various types of invocations: message, persuasion, description, approval, etc., to use a variety of questions, the ability to convey the content of what you read. Teaching a foreign language can make a significant contribution to the development of educational and communicative skills, since in the process of mastering speech in English, these skills, of necessity, become the object of increased attention.